(untitled) - Dent, David (Wageningen, 1986)
The book presents a series of recommandations to who are in a position to influence the course of land development and research. These provide a strategy for land reclamation and conservation that has been developed through consultation and detailed study
Quản lý và sử dụng đất có vấn đề
Keywords: Acid soils,Soil science